Development of IBSC (Investigation Based Science Collaborative) Based Student Worksheet on Human Respiratory System to Improve Science Literacy and Collaboration Skills of Grade XI Students - Prita Pratiwi Biantoro; Kartika Ratna Pertiwi (Postgraduate, University of Mataram, 2024)
In the 21st century, students need to have scientific literacy abilities and collaborative skills in order to be able to compete in this era. This study aims to knowing the validity, the practicality and to determine the effectiveness of IBSC (Investigation Based Science Collaborative) based student worksheet used as teaching materials on human respiratory system to improve student’s science literacy skills and collaboration skills. This development research was conducted using the ADDIE model and the data analysis used was the Manova test. The results of the study are the student worksheet is declared valid for use in the process of learning activities with an average validation score in the good category. Its also received a score in the very good category in terms of readability and practicality. The Manova test results showed a Sig. 0.000 with N-Gain values are 60.57 and 62,58 in fairly effective catefory which means there is a significant difference in the science literacy skills and collaboration skills of students who using and not using IBSC (Investigation Based Science Collaborative) based student worksheet.